The Impact of Bariatric Surgery on Nonalcoholic Steatohepatitis - Rabl, Charlotte; Campos, Guilherme M. (Seminars in Liver Disease, 2012)
Nonalcoholic steatohepatitis (NASH) is a stage of nonalcoholic fatty liver disease (NAFLD), and in most patients, is associated with obesity and the metabolic syndrome. The current best treatment of NAFLD and NASH is weight reduction with the current options being life style modifications, with or without pharmaceuticals, and bariatric surgery. Bariatric surgery is an effective treatment option for individuals who are severely obese (body mass index ≥ 35 kg/m2), and provides for long-term weight loss and resolution of obesity-associated diseases in most patients. Regression and/or histologic improvement of NASH have been documented after bariatric surgery. We review the available literature reporting on the impact of the various bariatric surgery techniques on NASH.
Keywords: Nonalcoholic steatohepatitis; nonalcoholic fatty liver disease; obesity; bariatric surgery; weight loss